Meeting The Needs Of Nurses In Efforts By The Spiritual Self Improvement Of Efficacy Of Patients With Terminal Disease In The Hospital Ward - Heri Saputro; Sri Astutik; Petrus Kondo; Cici Bagawanti (Universitas STRADA Indonesia, 2020)
This study research design Correlation Study with Cross Sectional approach. Technics sampling Simple random sampling with a sample of 21 respondents. The research instrument used questionnaire. Statistical data analysis Pearson correlation test. Most of the respondents 66.7% were spiritual needs. Nearly half of the respondents 57.1% (12 people) are not too sure will be able to live the rest of his life with better. Statistical test results obtained p-value was p = 0.006, which means reject Ho conclusion there is no relationship spiritual fulfillment by nurses in an effort to increase self efficacy of patients with terminal illness. Nurses provide spiritual fulfillment is better, then the patient will have the confidence that he is more meaningful or useful to others and be able to get closer to God Almighty and be ready at any time to die comes so spiritual fulfillment good nurse will help improve self efficacy of patients